Effectively integrating experiments into conservation practice. Issue 2 (24th May 2021) - Ockendon, Nancy; Amano, Tatsuya; Cadotte, Marc; Downey, Harriet; Hancock, Mark H.; Thornton, Ann; Tinsley‐Marshall, Paul; Sutherland, William J.
Abstract: Making effective decisions in conservation requires a broad and robust evidence base describing the likely outcomes of potential actions to draw on. Such evidence is typically generated from experiments or trials that evaluate the effectiveness of actions, but for many actions evidence is missing or incomplete. We discuss how evidence can be generated by incorporating experiments into conservation practice. This is likely to be most efficient if opportunities for carrying out informative, well‐designed experiments are identified at an early stage during conservation management planning. We consider how to navigate a way between the stringent requirements of statistical textbooks and the complexities of carrying out ecological experiments in the real world by considering practical approaches to the key issues of replication, controls and randomization. We suggest that routinely sharing the results of experiments could increase both the value for money and effectiveness of conservation practice. We argue that with early planning and a small additional input of effort, important new learning can be gained during the implementation of many conservation actions. Abstract : There are significant opportunities to generate important new evidence by routinely considering whether experiments can be incorporated into conservation practice. We discuss how to identify these opportunities and consider how to design practical and informative experiments to capitalise on them. 要旨: 1. 生物多様性保全において効果的な意思決定を行うためには、特定の対策がもたらす可能性のある効果についての広範で頑健な科学的根拠が必要となる。このような科学的根拠は対策の有効性を評価する実験や試験から得られるものの、保全の現場では利用できる科学的根拠が欠如しているか、根拠が得られても不完全であることが多い。 2. 本稿では、保全活動に実験的アプローチをより積極的に組み込むことで、どのように必要な科学的根拠が得られるようになるかについて考察を行った。どうすれば有益で適切に設計された実験が行えるかを保全管理計画の初期段階で理解しておくことが最も効率的であると考えられる。 3. 統計学の教科書では実験計画法について厳しい要求が行われている一方で、現場で行われる生態学的な実験には様々な複雑さが関わり、その中で反復や対照群、無作為化といった重要な問題に実際どのように取り組むべきかを考察した。 4. 日常的に実験結果を共有することで、保全活動の費用対効果と有効性の両方を高めることができるだろう。 5. 早期に計画を立て、わずかな労力を追加するだけで、多くの保全活動において重要な新しい知見を得ることができると考えられる。